ВОЗДЕЙСТВИЕ ИНТЕРНЕТ-КОММУНИКАЦИИ НА ИЗМЕНЕНИЕ КОГНИТИВНЫХ СТОРОН ЛИЧНОСТИ - Кененбаев, Е.Т. (SCIENCE and SOCIETY, 2024)
The article examines the degree of influence of Internet communications on the cognitive side of a virtual user of the electronic information field. The study was conducted from the perspective of the impact of transformation of linguistic categories in the communication process on the characteristics of user self-identification. The result of the study was the conclusion that these two sides of communication are significantly interdependent.